Odpowiedź :
3.
a)
[tex] \frac{4}{5} + \frac{1}{10} = \frac{8}{10} + \frac{1}{10} = \frac{9}{10} [/tex]
b)
[tex] \frac{1}{6} + \frac{2}{3} = \frac{1}{6} + \frac{4}{6} = \frac{5}{6} [/tex]
c)
[tex] \frac{2}{3} + \frac{1}{5} = \frac{10}{15} + \frac{3}{15} = \frac{13}{15} [/tex]
d)
[tex] \frac{4}{7} + \frac{1}{2} = \frac{8}{14} + \frac{7}{14} = \frac{15}{14} = 1 \frac{1}{14} [/tex]
e)
[tex] \frac{8}{9} - \frac{1}{ 3} = \frac{16}{18} - \frac{6}{18} = \frac{10}{18} [/tex]
f)
[tex] \frac{3}{10} - \frac{1}{5} = \frac{3}{10} - \frac{2}{10} = \frac{1}{10} [/tex]
g)
[tex] \frac{4}{5} - \frac{2}{3} = \frac{12}{15} - \frac{10}{15} = \frac{2}{15} [/tex]
h)
[tex] \frac{5}{7} - \frac{1}{4} = \frac{20}{28} - \frac{7}{28} = \frac{13}{28} [/tex]
i)
[tex]2 \frac{2}{5} + 3 \frac{1}{2} = 2 \frac{4}{10} + 3 \frac{5}{10} = 5 \frac{9}{10} [/tex]
j)
[tex]4 \frac{3}{7} + 2 \frac{2}{3} = 4 \frac{9}{21} + 2 \frac{14}{21} = 6 \frac{23}{21} = 7 \frac{2}{21} [/tex]
k)
[tex]2 \frac{3}{8} + 1 \frac{1}{6} = 2 \frac{9}{24} + 1 \frac{4}{24} = 3 \frac{13}{24} [/tex]
l)
[tex]4 \frac{1}{2} + 2 \frac{3}{5} = 4 \frac{5}{10} + 2 \frac{6}{10} = 6 \frac{11}{10} = 7 \frac{1}{10} [/tex]
m)
[tex]4 \frac{1}{4} - 2 \frac{2}{3} = 4 \frac{3}{12} - 2 \frac{8}{12} = 3 \frac{15}{12} - 2 \frac{8}{12} = 1 \frac{7}{12} [/tex]
n)
[tex]5 \frac{1}{9} - 1 \frac{5}{6} = 5 \frac{2}{18} - 1 \frac{15}{18} = 4 \frac{20}{18} - 1 \frac{15}{18} = 3 \frac{5}{18} [/tex]
o)
[tex]3 \frac{1}{15} - 1 \frac{1}{10} = 3 \frac{10}{150} - 1 \frac{15}{150} = 2 \frac{160}{150} - 1 \frac{15}{150} = 1 \frac{145}{160} = 1 \frac{29}{32} [/tex]
p)
[tex]5 \frac{5}{13} - 3 \frac{1}{2} = 5 \frac{10}{26} - 3 \frac{13}{26} = 4 \frac{36}{26} - 3 \frac{13}{26} = 1 \frac{23}{26} [/tex]
6.
a)
[tex] \frac{1}{2} + \frac{1}{3} + \frac{1}{4} = \frac{6}{12} + \frac{4}{12} + \frac{3}{12} = \frac{13}{12} = 1 \frac{1}{12} [/tex]
b)
[tex]1 \frac{2}{5} + 3 \frac{4}{10} + 2 \frac{1}{2} = 1 \frac{4}{10} + 3 \frac{4}{10} + 2 \frac{5}{10} = 6 \frac{13}{10} = 7 \frac{3}{10} [/tex]
c)
[tex]4 \frac{1}{3} - 2 \frac{2}{5} + 1 \frac{1}{5} = 4 \frac{5}{15} - 2 \frac{6}{15} + 1 \frac{3}{15} = 3 \frac{20}{15} - 2 \frac{6}{15} + 1 \frac{3}{15} = 1 \frac{17}{15} = 2 \frac{2}{15} [/tex]
d)
[tex]7 - 3 \frac{1}{3} - 2 \frac{1}{8} = 7 - 3 \frac{8}{24} - 2 \frac{3}{24} = 3 \frac{16}{24} - 2 \frac{3}{24} = 1 \frac{13}{24} [/tex]
e)
[tex]3 \frac{3}{4} - 2 \frac{2}{3} + 6 - 3 \frac{5}{6} = 3 \frac{9}{12} - \frac{8}{12} + 6 - 3 \frac{10}{12} = 3 \frac{1}{12} + 6 - 3 \frac{10}{12} = 2 \frac{13}{12} + 6 - 3 \frac{10}{12} = 8 \frac{13}{12} - 3 \frac{10}{12} = 5 \frac{3}{12} = 5 \frac{1}{4} [/tex]
f)
[tex]10 - (2 \frac{1}{9} - \frac{1}{2} + 1 \frac{5}{6} ) = 10 - ( 2 \frac{2}{18} - \frac{9}{18} + 1 \frac{15}{18} ) = 10 - (1 \frac{20}{18} - \frac{9}{18} + 1 \frac{15}{18} ) = 10 -( 1 \frac{11}{18} + 1 \frac{15}{18} )= 10 - ( \frac{29}{18} + 1 \frac{15}{18}) = 10 - 1 \frac{44}{18} = 10 - 3 \frac{8}{18} = 6 \frac{10}{18} = 6 \frac{5}{9} [/tex]
g)
[tex](4 \frac{1}{3} - 2 \frac{2}{5} ) - (6 \frac{3}{5} - 5 \frac{2}{3} ) =(4 \frac{5}{15} - 2 \frac{6}{15} ) - (6 \frac{9}{15} - 5 \frac{10}{15} ) =( 3 \frac{20}{15 }- 2 \frac{6}{15}) - (5 \frac{24}{15} - 5 \frac{10}{15} ) = 1 \frac{14}{15} - \frac{14}{15} = 1[/tex]
h)
[tex]3 \frac{1}{4} + 2 \frac{2}{5} - (4 \frac{1}{3} - 2 \frac{2}{3} ) = 3 \frac{5}{20} + 2 \frac{8}{20} - (3 \frac{4}{3} - 2 \frac{2}{3} ) = 5 \frac{13}{20} - 1 \frac{2}{3} = 5 \frac{39}{60} - 1 \frac{40}{60} = 4 \frac{99}{60} - 1 \frac{40}{60} = 4 \frac{59}{60} [/tex]
Myślę że pomogłem ;)